Endogeneities of optimum currency areas: what brings countries sharing a single currency closer together? - Paul De Grauwe; Francesco Paolo Mongelli (European Central Bank (ECB), 2005)
This paper brings together several strands of the literature on the endogenous effects of monetary integration: i.e., whether sharing a single currency may set in motion forces bringing countries closer together. The start of EMU has spurred a new interest in this debate. Four areas are analysed: the endogeneity of economic integration, in which we look primarily at evidence on prices and trade; the endogeneity of financial integration or equivalently of insurance schemes based on capital markets; the endogeneity of symmetry of shocks; and the endogeneity of product and labour market flexibility. We present diverse arguments and, where possible, explore the incipient empirical literature focussing on the euro area. Our preliminary conclusion is one of moderate optimism. The different endogeneities that exist in the dynamics towards optimum currency areas are at work. How strong these endogeneities are and how quickly they will do their work remains to be seen.
Keywords: E42; F13; F33; F42; 330; Economic and Monetary Integration and EMU; Optimum Currency Area; Optimaler Währungsraum; Regionale Wirtschaftsintegration; Eurozone; EU-Staaten; Wirkungsanalyse